New Concept for Dual-Layer Hydrophilic/Hydrophobic Composite Membrane for Membrane Distillation - Bilad, Muhammad R.; Al Marzooqi, Faisal A.; Arafat, Hassan A. (Journal of Membrane and Separation Technology, 2015)
This study presents a new concept of a simple method for the synthesis of dual layer hydrophilic/hydrophobic composite membranes for membrane distillation (MD). The membranes were prepared of poly(vinylidenefluoride) (PVDF) by phase inversion. The synthesis was realized by allowing a full or partial penetration of the polymer solution through one or two non-woven support (NWS) layers. This was achieved by proper selection of a thin NWS having high stiffness, high porosity and low surface tension, in combination with a runny polymer solution and sufficient time gap between casting and coagulation. The applied preparation method was effective in yielding dual layer composite membranes. The first layer atop the NWS was a hydrophilic or slightly hydrophobic one (contact angle (CA) of 88-92º), while the bottom layer beneath the NWS was highly hydrophobic (CA=132-140º). The difference in surface energy between the top and bottom layers originated from a difference in morphology. A smooth and dense top layer is formed as a result of an instantaneous demixing, while a porous and multi-scale network with some degrees of spherulitical structure was formed on the bottom by a delayed demixing mechanism. Direct contact MD (DCMD) results showed that the obtained flux was comparable to other composite MD membranes with high salt rejection. Membrane alignment inside the MD module is a critical element in determining the membrane performance and is shown to significantly increase flux when a top facing feed configuration is used.